Development of double labeling in situ hybridization using RNA probes for genome detection of nervous necrosis virus (NNV). (December 2018) - Kim, Jae-Ok; Kim, Jong-Oh; Kim, Soo-Jin; Kim, Wi-Sik; Oh, Myung-Joo
Abstract: In situ hybridization (ISH) of genomic segments using RNA-RNA hybrid for nervous necrosis virus (NNV) detection has not been reported yet. The objective of this study was to develop RNA-ISH using RNA probes for the detection of NNV in infects SSN-1 cells or sevenband grouper Hyporthodus septemfasciatus . Two viral RNA segments viz., RNA1 and RNA2 were synthesized by in vitro transcription and labeled with fluorescein UTP and dignoxigenin dUTP, respectively. These labeled RNA probes specifically detected NNV in infected SSN-1 cells. We also applied double labeling RNA-ISH with two-color staining of RNA probes. The results showed that these two viral genomic segments were localized in same regions although RNA1 was also expressed separately. These findings suggest that RNA1 overexpression may be important for sufficient assembly of infectious particles. The RNA-ISH showed that both RNA segments were localized in the tectum opticum, torus semicircualris, cerebellum, thalamus, hypothalamus, and medulla of experimentally infected brain tissues. Especially, RNA segments were highly localized around the ventricle, suggesting that ventricle might play a vital role in the spread of NNV. This technique can be useful for understanding the localization of NNV and the relationship between clinical sign and viral expression. Highlights: This study is the first to develop a RNA-ISH for the localization of NNV segment in infected SSN-1 cells and brain tissues. RNA1 gene was separately detected in infected cell and brain tissues using double labeling RNA-ISH. The NNV genomic segments were localized in the medulla, thalamus, hypothalamus and cerebellum in infected brain tissues. RNA segments were highly localized around the ventricle, which seem to important role in the spread of NNV.